A 3D Cu‐Naphthalene‐Phosphonate Metal–Organic Framework with Ultra‐High Electrical Conductivity. (2nd October 2020) - Peeples, Craig A.; Kober, Delf; Schmitt, Franz‐Josef; Tholen, Patrik; Siemensmeyer, Konrad; Halldorson, Quinn; Çoşut, Bünyemin; Gurlo, Aleksander; Yazaydin, Ahmet Ozgur; Hanna, Gabriel; Yücesan, Gündoğ
Abstract: A conductive phosphonate metal–organic framework (MOF), [{Cu(H2 O)}(2, 6‐NDPA)0.5 ] (NDPA = naphthalenediphosphonic acid), which contains a 2D inorganic building unit (IBU) comprised of a continuous edge‐sharing sheet of copper phosphonate polyhedra is reported. The 2D IBUs are connected to each other via polyaromatic 2, 6‐NDPA's, forming a 3D pillared‐layered MOF structure. This MOF, known as TUB40, has a narrow band gap of 1.42 eV, a record high average electrical conductance of 2 × 10 2 S m −1 at room temperature based on single‐crystal conductivity measurements, and an electrical conductance of 142 S m −1 based on a pellet measurement. Density functional theory (DFT) calculations reveal that the conductivity is due to an excitation from the highest occupied molecular orbital on the naphthalene‐building unit to the lowest unoccupied molecular orbital on the copper atoms. Temperature‐dependent magnetization measurements show that the copper atoms are antiferromagnetically coupled at very low temperatures, which is also confirmed by the DFT calculations. Due to its high conductance and thermal/chemical stability, TUB40 may prove useful as an electrode material in supercapacitors. Abstract : Electrically conductive metal‐organic frameworks (MOFs) have the potential to be used as electrode materials for supercapacitors. Herein, a copper phosphonate MOF with a narrow band gap and record high conductance, is reported. Calculations suggest that the conduction is due to excitations from the highest occupied molecular orbitals on the naphthalene linkers to the lowest unoccupied molecular orbitals on the copper atoms.